Clinical Profile and In-hospital Outcome of Acute Household Substances Poisoning in a Tertiary Care Hospital: Household Substances Poisoning (Bangladesh Journal of Medicine, 2024)
Background: Poisoning is an acute medical emergency. Among the thousands of harmless products available for household, very few are hazardous. Still, self-poisoning with these substances is one of the commonest mode of poisoning. This study was carried out to get information related to clinical profile and inhospital outcome of household substances poisoning in a particular area of Bangladesh. Methods: This cross-sectional type of descriptive study was carried out in the department of Medicine, Sylhet M.A.G. Osmani Medical College Hospital, Sylhet, Bangladesh during the period of June 2022 to November 2022.Purposive convenient sampling was applied to recruit sample from study population. Calculated sample size was 64. Detailed history including nature of poisoning (unintentional/ intentional), route of poisoning, type of poison, symptoms and signs with relevant laboratory findings were documented in a structured data collection sheet through interview from the patient or their guardians after obtaining informed written consent. In-hospital outcome in terms of survival (discharged, discharge without advice/absconded) and mortality were recorded.Results:Among 64 participants majority 65.63% (n=42) were female and most 56.25% (n=36) were of 18-20 years age group.Regarding educational status 96.87 %(n=62) participants were educated. All of the poisoning were intentional and by oral route. Harpic was the most common agents 59.38% (n=38) used by the victims.Vomiting was the most common 81.25% (n=52) symptomand oral ulcer was the commonest 40.63% (n=26) sign. No significant abnormality of vital signs and laboratory investigations were found. Majority of the respondents 43.75 % (n=28) stayed 2 days in hospital for treatment purpose. Total 85.94% (n=55) respondents were discharged with advice and 14.06% (n=9) respondents left hospital without medical advice. No death was documented in this study. Conclusion: Young teenaged female patients were the majority of victims in our study reflecting the degree of powerlessness and hopelessness of young, educated people with unemployment and difficulties in coping with life stressors.Bangladesh J Medicine 2024; 35: 70-75